LARANGAN SEBAGAI MEDIA PELESTARIAN HUTAN PADA KOMUNITAS ADAT CIKONDANG - Lasmiyati Lasmiyati; Ria Intani Tresnasih (Jurnal Analisis Kebijakan Kehutanan, 2023)
This research is conducted because of the frequent forest destruction occurrence, meanwhile, the forests in the Cikondang  Indigenous  Community  area  are  still  wellpreserved  to  date.  This  study  aims  to  obtain  an  overview of the sacred grove located in Cikondang, the reason why the forest is designated as a sacred grove, and the factors  that  cause  the  forest  to  be  well-preserved.  This  research  is  a  descriptive  one  by  exercising  the  qualitative method.  The  qualitative  method  isused  to  analyze  objects  that  cannot  be measured  using  numbers.  The  research methods were conducted by literature studies, observations, and interviews. Informants, both key and additional,were interviewed with reference to interview guidelines. The research stage is initiated by extracting the data in the field, classifying and analyzing the data, and finally drawing a conclusion. The results indicated that the forests in Cikondang  physically  have  similarities  with  forests  in  general.  Historical  events  and  awareness  of  the  benefits  of the forest designated the forest as a sacred grove whose preservation has been well-maintained due to the enactment of a number of forbiddance or pamali related to the existence of the forest. Forbiddance or pamali is a customary rule that is obeyed because of fear of violating the forbiddance or pamali. It has the "power" to prevent people from causing forest destruction. Forbiddance or pamali can be a means to preserve the forest.